Comparison of colour properties in american walnut (Juglans nigra) wood coated with different surface finishes - Ümit Ayata (Les)
In this research, the colour characteristics [hue (ho) angle, yellow (b*) colour tone, lightness (L*), red (a*) colour tone, chroma (C*), ∆E*, ∆L*, ∆a*, ∆b*, ∆C*, and ∆H*] of surfaces treated with three distinct types of coatings [solvent-based yacht varnish, which has high hardness and is highly resistant to water, a waxy varnish formulated for interior and exterior wood coatings, consisting of a mixture of natural oils, waxes, and resins, and matte-glossy, solvent-based, acrylic resin-based stone varnish)] on American walnut (Juglans nigra L.) wood were examined and compared. When all types of varnishes are applied to wooden surfaces, decreases in b*, C*, ho, and L* values were observed, while increases in a* values were detected. Reviewing the ∆E* values, 13.59 was identified for stone, 16.62 for yacht, and 12.40 for waxy varnish. Upon examination of the ∆H* values, they were determined as 4.72 for stone, 5.06 for yacht, and 3.42 for waxy varnish. The highest values for the parameters L*, b*, C*, and ho, and the lowest value for a*, were determined on the control experimental samples (without any varnish application). In the study, it was observed that the coating types, each with different chemical compositions, yielded different results.